Tinjauan Yuridis Terhadap Putusan KPPU No. 05/KPPU-1/2005 Mengenai Penguasaan Pasar (Pelaksanaan Sistem Pelaporan Elektronik Antara Bursa Efek Jakarta dengan PT. Limas Stockholmindo) (Lex Jurnalica, 2009)
Effort emulation in happening business activity because party which do business activity gets gain procurement and remove loss. To that is effort agent utilizes to make the point whatever to get that gain despite makes the point that is utilized gets to evoke emulation not well. Therefore Indonesia government tries to manage that emulation in walking business activity corresponds to specified regulation which is UU NO. 5 Years 1999 about Practice Prohibition Monopolizes and Insanitary Effort emulations. Although UU No. 5 Years 1999 was established and has explicit sanction, extant effort agent that breaches and do emulation not well as case among Jakarta Stock Exchange and PT. Stockholmindo's pyramid in mastery market by undertaking discrimination practice. Writer tries to describe that case and analyses KPPU'S verdict (Effort emulation commission) one that given unto by Jakarta Stock Exchange and PT. Stockholmindo's pyramid, there is method even that is utilized is normatif that gets descriptive character. In system per-forming monitoring  and e reporting  Exclusive as Jakarta stock exchange points directly PT. Stockholmindo's pyramid without give chance to vendor who have performance and as as concept PT. Stockholmindo's pyramid, really in conflict with procedure tender already being established by BAPEPAM(Capital Market Supervisor body) where in that process Stock Exchange Jakarata shall invite vendor or entrepreneur real time's service and Jakarta Stock Exchange pass on system performing IDE e reporting  and monitoring one that agreed-on by BAPEPAM (Capital Market Supervisor body) and Emiten's Association Indonesian to vendor, on chance it also vendor can propose system development concept e reporting  and monitoring , technical facet and price who will be put on to recorded firm that utilizes system  e reporting and monitoring.  In process  that Jakarta Stock Exchange also arranges feasibility study to vendor one that attending. Stock Exchange afterwards Jakarta can point vendor one that will perform both of that system and has to be agreed by attending party and diumukan to publics. Stock exchange Jakarta not do specified procedure by BAPEPAM and does exclusive ala directing to PT. Stockholmimndo's pyramid,   therefore direct directing conduct that dikategorikan can skulduggery or insanitary emulation as arranged in UU No. 5 Years 1999 about Practice Prohibition Monopolizes and insanitary Effort emulations,  where is Jakarta Stock Exchange was evident breach aught elements on section 19 fonts d. by apply discriminatory to other effort agents,  intention from it is pointing direct one be done By Stock Exchange to PT's Jakarta. Stockholmindo's pyramid that begets service firm real time  information  another or so-called vendor don't get chance for competing healthy ala with PT.Stockholmindo's pyramid,eventually vendor that have concept that equals PT. Stock-holmindo's pyramid to performing system e reporting and monitoring. Effect of pointing direct that therefore Jakarta Stock Exchange stricken down by Sanction by an Effort emulation Com-mission commisioned to act explicit effort agent that breach rule on UU No. 5 Years 1999 about Practice Prohibition Monopolizes and Insanitary Effort emulations. Jakarta stock exchange was evident breach section 19(d) UU No. 5 Years 1999 about Practice Prohibition Monopolizes and Insanitary Effort emulations which is discrimination act to other effort agents therefore sanction which be put on to Jakarta Stock Exchange and PT. Pyramid Stockholmindo is by discontinue all electronic reporting system activity with cancel agreement already disepakati by Jakarta Stock Exchange with PT. Stockholmindo's pyramid, sanction that gave by KPPU to Jakarta Stock Exchange and PT. Stockholmindo's pyramid constitute sanction that gets administrative character correspond to kewenangan KPPU, although in UU No. 5 Years 1999 said available pidana's sanctions liable to section 19d. Keywords: KPPU Verdict, Market Mastery, Electronic Reporting System